PENGARUH INTENSITAS CAHAYA TERHADAP PERTUMBUHAN DAN KONTEN RANTAI PANJANG POLYISOPRENOID PADA MANGROVE SEJATI MAYOR BERJENIS SEKRESI Sonneratia caseolaris (L.) - Epifani Natalia Gultom; Mohammad Basyuni; Budi Utomo (Program studi Kehutanan USU, 2015)
Each plant species has a different response to the light intensity. Some species need shade in the early growth, and there are species did not require shade in the early growth. Mangrove degradation have been occurred for recent years, rehabilition program therefore are needed for reforestation. The reforestation needs a superior and qualified seeds for the best growth. This study focus on S. caseolaris because this fruit species priority consumed by local people in the area of mangrove and for rehabilitation program. The applied research method is Complete Random Sampling, non factorial that consist of different repetition. The applied analysis method is variance analysis with advanced tesdt by determining the value that influence or not with Dunnet method on confidential level 5% with 4 treatments for light intensity 100%, 75%, 50% and 25%. This research was conducted at Pharmacy Laboratory and Faculty of Agriculture, Department of Forestry of University of Sumatera Utara since July of 2014 to January of 2015. The results of research indicates that the light intensity 50% showed best growth of morphology and polyisoprenoid content is not found in S. caseolaris because the dried weight is not sufficient for further analysis. Keywords : Light Intensity, Morphology, S. caseolaris